Examining Construct Validity of the Student Online Learning Readiness (SOLR) Instrument Using Confirmatory Factor Analysis - Yu, Taeho (Online Learning, 2019)
This study examines the construct validity of the Student Online Learning Readiness (SOLR) instrument. The SOLR instrument consists of 20 items to evaluate social competencies, communication competencies, and technical competencies in online learning. A large Midwestern university was selected to test the construct validity of the SOLR instrument. A total of 347 undergraduate students participated in this study. Confirmatory factor modeling approach was used to assess the construct validity of the SOLR instrument for this study. As a result of Confirmatory Factor Analysis (CFA), the hypothesized model of 20-item structure of the SOLR instrument was verified as a good fit for the data (χ2 (164, N=347)=1959.94, p<.001, IFI=.81, CFI=.81, GFI=.55, RMSEA=.016).